2021
DOI: 10.1016/j.isci.2021.102224
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking DKK1 in T cells exhibit high bone mass and are protected from estrogen-deficiency-induced bone loss

Abstract: Summary The Wnt inhibitor Dickkopf-1 (DKK1) is a negative regulator of bone formation and bone mass and is dysregulated in various bone diseases. How DKK1 contributes to postmenopausal osteoporosis, however, remains poorly understood. Here, we show that mice lacking DKK1 in T cells are protected from ovariectomy-induced bone loss. Ovariectomy activated CD4+ and CD8+ T cells and increased their production of DKK1. Co-culture of activated T cells with osteoblasts inhibited Wnt signaling in osteoblasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 84 publications
1
10
0
Order By: Relevance
“…In addition, miR-1278 was positively associated with sclerostin and Dkk1, which are inhibitors of the WNT signaling pathway. These associations are in concordance with previous studies on the association between inhibitors of the WNT signaling pathway and estrogen status (40)(41)(42)(43)(44). The Wnt/ b-catenin pathway activation enhances bone mass not only by stimulating osteoblastogenesis but, at least to some extent, also by inhibiting osteoclastogenesis as well (44).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, miR-1278 was positively associated with sclerostin and Dkk1, which are inhibitors of the WNT signaling pathway. These associations are in concordance with previous studies on the association between inhibitors of the WNT signaling pathway and estrogen status (40)(41)(42)(43)(44). The Wnt/ b-catenin pathway activation enhances bone mass not only by stimulating osteoblastogenesis but, at least to some extent, also by inhibiting osteoclastogenesis as well (44).…”
Section: Discussionsupporting
confidence: 92%
“…Among these, IGF1 activates phosphoinositide 3-kinase (PI3K)/Akt mammalian target of rapamycin (mTOR) pathway, with subsequent breast cancer cell growth, proliferation, and migration into the bone [17,61,62]. Osteoblasts can also be regulated by metastatic tumor cell-derived factors including endothelin 1 (ET1), dickkopf 1 (DKK1), and the Wnt signaling cascade [36,[63][64][65][66]. While Wnt promotes osteoblast differentiation, its activity can be inhibited by DKK1, which is an antagonist in this cascade.…”
Section: Biological Mechanisms Of Bone Metastasismentioning
confidence: 99%
“…The expression of DKK1 in CD4 + and CD8 + T cells was increased in ovariectomized mice. No literature has reported the correlation between LINGO2 and GTF2H4 and estrogen [ 63 ]. Our findings suggested that the estrogen signaling pathway might affect the progression and prognosis of LUAD by regulating the expression of these four genes.…”
Section: Discussionmentioning
confidence: 99%